2020
DOI: 10.1111/ans.16392
|View full text |Cite
|
Sign up to set email alerts
|

Non‐operative management for small bowel obstruction in a virgin abdomen: a systematic review

Abstract: Background Small bowel obstruction (SBO) is a common general surgical presentation and there has been a shift towards non‐operative management (NOM) for patients with previous abdominal surgery. Historically, exploratory surgery has been mandated for SBO in patients with a virgin abdomen. However, there is increasing evidence for NOM in this group of patients. Methods A systematic review was performed according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. A search was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…Although small bowel obstruction in a virgin abdomen has traditionally been thought to be a surgical emergency with requirement for surgical intervention, recent reports in the literature have shown increasing evidence for non‐operative management in a selected group of patients with no features of closed loop small bowel obstruction 10 . This case highlights the significance of Meckel's diverticulum as a potential cause of small bowel obstruction, and the possibility of this being associated with rare internal omental defects.…”
Section: Figmentioning
confidence: 84%
“…Although small bowel obstruction in a virgin abdomen has traditionally been thought to be a surgical emergency with requirement for surgical intervention, recent reports in the literature have shown increasing evidence for non‐operative management in a selected group of patients with no features of closed loop small bowel obstruction 10 . This case highlights the significance of Meckel's diverticulum as a potential cause of small bowel obstruction, and the possibility of this being associated with rare internal omental defects.…”
Section: Figmentioning
confidence: 84%
“…Indeed, the literature reports a high rate of surgery for these patients (39–83%), while their management should be the same as in managing aSBO with other causes [24]. Recent literature reports that previous surgery was an independent predictor of the success of non‐operative management (OR = 0.47; p = 0.03) [25], while conservative management seems feasible and safe in cases of aSBO in a previously un‐operated abdomen [26, 27]. Conservative management in such patients should, however, be pursued with caution because reviews include patients with aSBO in a virgin abdomen owing to indications other than aSBO.…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel obstruction in patients with a virgin abdomen (SBO-VA) have historically been operative situations due to the belief that more sinister etiologies are behind the obstruction [8,9]. Compared to the roughly 30% operative rate for adhesive SBO, SBO-VA have a reported operative rate of between 40-100% [8,9]. Recent systematic reviews have demonstrated mandatory operation may no longer be the case [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%